Orthodontic and prosthodontic management of an adult patient with unilateral cleft lip and palate - Sapna Singla; Puneet Kaur Pandher; Gurvanit Lehl; Manjit Talwar (Wolters Kluwer Medknow Publications, 2016)
Cleft lip and palate is a common congenital malformation. Individuals born with this type of deformity, face number of challenges such as facial esthetics, hearing impairment, anatomical deformities to name a few. These patients require various treatments involving a multidisciplinary team such as prosthodontists, orthodontists, cosmetic dentists and surgeons. This report describes a case of orthodontic and prosthetic rehabitilation of an adult patient with unilateral cleft lip and palate.